Extinction and quasi-stationarity in the stochastic logistic SIS model - Nêasell, Ingemar (Lecture notes in mathematics Mathematical biosciences subseries, 2011)
This volume presents explicit approximations of the quasi-stationary distribution and of the expected time to extinction from the state one and from quasi-stationarity for the stochastic logistic SIS model. The approximations are derived separately in three different parameter regions, and then combined into a uniform approximation across all three regions. Subsequently, the results are used to derive thresholds as functions of the population size N